Knowledge and Attitude among Community Pharmacists regarding Pharmacovigilance – A Cross Sectional Survey - MT Ghozali; Intan Waskita Murni (Indonesian Journal of Pharmacy, 2023)
The adverse drug reaction reporting system or pharmacovigilance, as a part of post-marketing surveillance, is the responsibility of every country and national government. Therefore, optimization of knowledge and attitude regarding the system were very essential. This study aimed to examine the relationship between knowledge and attitude regarding pharmacovigilance among pharmacists working in public healthcare services in the rural area. This study was a cross-sectional analytical observational research involving 48 hospital and community pharmacists carried out from July to December 2021 at Bantul Regency, Yogyakarta, Indonesia. Descriptive statistics and frequency distribution analysis were conducted to obtain an overview of knowledge and attitude regarding pharmacovigilance system, while chi-square examined the relationship between them. The results showed that 60.4% of participants had good knowledge, and 52.1% had a positive attitude regarding the system. It was also confirmed that there was a relationship between knowledge and attitude with a p-value of 0.045. Therefore, there was a relationship between knowledge and attitude regarding pharmacovigilance among pharmacists working in rural public healthcare. Based on the results of this study, it was highly recommended for healthcare practitioners, especially pharmacists, to learn and practice pharmacovigilance in their respective practice.